Employing Interface Compensators to Enhance the Power Quality In Hybrid AC/DC Microgrids - Dehnavi, Saeed Daneshvar; Shahparasti, Mahdi; Simab, Mohsen; Mortazavi, Seyed Mohammad Bagher (Ciência e Natura, 2015)
After the introduction of distributed generators, regarding the challenges these networks face, employing AC/DC Hybrid microgrids would be an undeniable issue due to its many advantages and it will certainly find a significant position. Thus, discussing the power quality in this type of microgrids and clean power for feeding the load via this microgrid is a drastic challenge. This paper proposing a hybrid microgrid with 2 interface converters, one placed in series and the other placed in parallel, tries to accomplish these control objectives in an AC microgrid in order to improve power quality: input sine current with Cosϕ=1 and output sine voltage with normal value when source voltage is abnormal and non-sinusoidal, besides, non-linear loads’ presence. Simulation results verify the favorable performance of converters and effective functionality of control systems.